Peran Masyarakat Adat Dalam Menjaga Dan Melestarikan Lingkungan Hidup - Noya, Ekberth Vallen (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: This article outlines an analysis of the role of indigenous communities in protecting and preserving the environment through the traditional Kewang institution, so that the implementation of Sasi can run well.Purposes of the Research: The purpose of this article is to look at the role of indigenous communities in protecting and preserving the environment based on applicable customary law.Methods of the Research: The method used in this research is normative juridical which focuses on the main law by examining theories, concepts, legal principles and statutory regulations related to this research.Results of the Research: Environmental awareness is awareness that arises from an understanding of the relationship between humans and their environment. Awareness that humans are an integral part that cannot be separated from their environment is the key to successful environmental management. Through this understanding, on the one hand, it is hoped that good and healthy environmental quality will be realized as one of the constitutional rights of citizens as regulated in Article 28H of the 1945 Constitution. Community participation as an effort to protect the law can be seen in the applicable regulations. Indigenous communities in their role of protecting the environment, the Kewang institution has a big role, through Sasi, the kewang can carry out the function of protecting and preserving the environment.